Effect of chemical pretreatment on the physical properties of dehydrated grapes - Gabas, A. L.; Menegalli, F. C.; Telis-Romero, J. (Marcel Dekker Inc, 1999)
The effects of chemical pretreatment and air drying temperature on drying kinetics, shrinkage, density and rehydration ratio of grapes were determined at various moisture contents. It was observed that the chemical pretreatment employed - a solution of 2% CaCO3 with 0 to 3% ethyl oleate - increased considerably the drying rate. It was established that the shrinkage increased with drying temperature between 40 to 80 degrees C and decreased with increasing concentration of ethyl oleate in the chemical pretreatment solution.
Keywords: density; drying; grape; pretreatment; rehydration ratio; shrinkage coefficient